Temporary Layoffs, Loss-of-Recall, and Cyclical Unemployment Dynamics - Gertler, Mark; Huckfeldt, Christopher; Trigari, Antonella (American Economic Review, 2026)
We revisit the role of temporary layoffs in the business cycle. While some have emphasized a stabilizing effect due to recall hiring, we quantify from the data an important countercyclical destabilizing effect due to “loss-of-recall,” whereby workers in temporary-layoff unemployment lose their job permanently. We develop a quantitative model allowing for endogenous flows of workers across employment and both temporary-layoff and jobless unemployment. The model captures both pre- and post-pandemic unemployment dynamics, including the contractionary role of loss-of-recall. We use our structural model to show that the Paycheck Protection Program generated sizable employment gains, in part by significantly reducing loss-of-recall. (JEL E24, E32, I12, J41, J63, J64)